Controlling the self-folding of a polymer sheet using a local heater: the effect of the polymer–heater interface. Issue 21 (21st April 2017) - Cui, Jianxun; Yao, Shanshan; Huang, Qijin; Adams, John G. M.; Zhu, Yong
Abstract : We controlled the folding direction and angle of a heat shrinkable polymer sheet by tailoring its mechanical interaction with a flexible heater. Abstract : Self-folding of a pre-strained shape memory polymer (SMP) sheet was demonstrated using local joule heating. Folding is caused by shrinkage variation across the thickness of the SMP sheet. The folding direction can be controlled by the interfacial interaction between the heater and the SMP sheet. When the heater is placed on the SMP sheet with no constraint (weak interface), the SMP sheet folds toward the heater. Temperature gradient across the SMP thickness gives rise to the shrinkage variation. By contrast, when the heater is fixed to the SMP sheet (strong interface), the SMP sheet can fold away from the heater. In this case shrinkage variation is dictated by the constraining effect of the heater. In either mode, 180 degrees folding can be achieved. The folding angle can be controlled by varying the heater width and folding time. This method is simple and can be used to fold structures with sharp angles in a sequential manner. A variety of structures were folded as demonstrations, including digital numbers 0–9, a cube, a boat, and a crane.